An Examination of Cross-Resistance to Photodynamic Therapy and Ultraviolet Light in Rodent Cells using a Viral Capacity Assay - Di Prospero, Lisa (My University, 1994)
Photodynamic therapy (PDT) for cancer utilizes the localised delivery of light to activate a photosensitizing drug (such as Photofrin) which is selectively retained by tumour tissues. Although this treatment modality is undergoing clinical trials, the mechanism of PDT cytotoxicity is not fully understood. One approach to understanding the mechanism of action of PDT is to study cell mutants showing alterations in their response to PDT. The capacity of mammalian cells to support virus replication has been used as an assay to compare cellular response to ultraviolet (UV) light and other cytotoxic agents. Cellular capacity has been previously employed to measure cellular recovery following UV irradiation and to predict the sensitivity of cells to several anticancer drugs. In this work, I have examined the use of the capacity assay to examine the sensitivity of cells to PDT treatment. RIF-1 mouse fibrosarcoma cells and a PDT resistant derivative, RIF-8A; as well as Chinese hamster ovary (CHO) cells and CHOMDR (multi-drug resistant) mutant cells were studied. Consistent with the clonogenic survival of these cells after PDT, the viral capacities of RIF-8A and CHO-MDR cells· were greater than those of RIF-1 and CHO cells respectively following PDT treatment. The capacity assay was also used to examine the relative ability of RIF cells to recover from PDT damage. These capacity experiments show that recovery from PDT damage is greater in RIF-SA cells compared to RIF-1 cells, suggesting that RIF-SA cells have an enhanced repair capacity for PDT damage compared to RIF-1 cells. The response of CHO cells and the RIF cells to ultraviolet (UV) light irradiation was also examined. No difference in the UV sensitivity of CHO-N and CHO-MDR cells was found. However, the RIF-SA cell line showed a cross-resistance to UV. The survival of viral DNA synthesis for UV-irradiated virus was also greater in RIF-SA cells compared to RIF-1 cells, suggesting that RIF-SA cells have an increased capacity for the repair of UV-induced DNA damage. It is possible that the increased resistance to PDT of RIF-SA may also result from an increased repair of POT-induced DNA damage in RIF-SA cells. The identification and characterization of a POT-sensitive cell mutant was also investigated. The CHO-AUXB1 cell mutant was found to show an increased sensitivity to PDT and UV compared to the CHO-PRO- parent line. This sensitivity of the CHO-AUXB1 mutant may also result from a deficiency in the repair mechanism of PDT-induced and UV-induced damage.
Keywords: cross-resistance; photodynamic therapy; ultraviolet light; rodent cell; viral capacity assay